Cinematics influence on the cyclic fatigue resistance of rotatory instruments in original system and a replica type. - Barreto, Vicente (2022)
Objective: To evaluate the resistance to cyclic fatigue of a replica rotary system in comparison with its original system. Method: F2 rotary instruments (n=19 per group) from the original brand ProTaper Gold system (Dentsply Maillefer, Ballaigues, Switzerland) were compared with a Super File III instrument (n=19 per group) from a Denco replica system (Medical Co., Shenzhen, China) regarding cyclic fatigue strength. The instruments were randomly distributed into two groups, according to the file brand. Subsequently, the fatigue cycle was measured; for which, they were activated using the E-mate Pro motor of the Denco brand (Medical Co., Shenzhen, China) at continuous rotation 300 rpm and a torque of 2.5 Ncm. Results: The fracture resistance time was recorded and statistically compared between both groups according to the type of instrument (original system/replica system) using the t-test for independent samples. Statistical analysis showed a significantly longer time to fracture for the replica system with an average of 588.8 ± 178.1 seconds; while, for the original system, the average fracture resistance time was 208.1 ± 41.9 seconds. The instruments of the replica system showed a significantly higher fracture toughness time compared with the instruments from the original system in rotary motion (p<0.05). Conclusion: The instruments of the replica system showed greater resistance to cyclic fatigue than the instruments of the original system.